2012
DOI: 10.1371/annotation/c6c16a43-aadd-4cd3-a916-e935534dab38
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Cell-Cycle Inhibition by Helicobacter pylori L-Asparaginase

Abstract: Helicobacter pylori (H. pylori) is a major human pathogen causing chronic gastritis, peptic ulcer, gastric cancer, and mucosaassociated lymphoid tissue lymphoma. One of the mechanisms whereby it induces damage depends on its interference with proliferation of host tissues. We here describe the discovery of a novel bacterial factor able to inhibit the cell-cycle of exposed cells, both of gastric and non-gastric origin. An integrated approach was adopted to isolate and characterise the molecule from the bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Asparaginase also changes asparagine into aspartic acid, so the lower level of asparagine might be also explained by the upregulation of asparaginase activity in the H. pylori-infected AGS cells.Asparagine enhances the proliferation of cancer cells[28], and therefore, asparaginase has been used as an anti-cancer drug. In addition, H. pylori also possesses its own asparaginase, and it was suggested that H. pylori asparaginase is a novel antigen that functions as a cell-cycle inhibitor of fibroblasts and gastric cells[29]. Therefore, H.pylori asparaginase might have contributed to the reduction in the level of asparagine seen in the H. pylori-infected AGS cells.…”
mentioning
confidence: 99%
“…Asparaginase also changes asparagine into aspartic acid, so the lower level of asparagine might be also explained by the upregulation of asparaginase activity in the H. pylori-infected AGS cells.Asparagine enhances the proliferation of cancer cells[28], and therefore, asparaginase has been used as an anti-cancer drug. In addition, H. pylori also possesses its own asparaginase, and it was suggested that H. pylori asparaginase is a novel antigen that functions as a cell-cycle inhibitor of fibroblasts and gastric cells[29]. Therefore, H.pylori asparaginase might have contributed to the reduction in the level of asparagine seen in the H. pylori-infected AGS cells.…”
mentioning
confidence: 99%